4-(2-Methoxyphenyl)piperazin-1-ium 6-chloro-5-isopropyl-2,4-dioxopyrimidin-1-ide - A. M. Al-Omary, Fatmah; A. Ghabbour, Hazem; A. El-Emam, Ali; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
In the cation of the title salt, C11H17N2O+.C7H8ClN2O2 -, the piperazine ring adopts a distorted chair conformation and contains a positively charged N atom with quaternary character. Its mean plane makes a dihedral angle of 42.36 (8) with the phenyl ring of its 2-methoxyphenyl substituent. The 2,4-dioxopyrimidin-1-ide anion is generated by deprotonation of the N atom at the 1-position of the pyrimidinedione ring. Intramolecular C—H...O hydrogen bonds generate S(6) ring motifs in both the cation and the anion. In the crystal, N—H...O, N—H...N and C—H...O hydrogen bonds are also observed, resulting in a twodimensional network parallel to the ab plane. The crystal stability is further consolidated by weak C—H...n interactions.